(untitled) (Música Hodie, 2023)
Opera performances are a collection of dialogues, dances, and songs, accompanied by a variety of instruments. The paper primarily focuses on the specific features of the influence of various Chinese violins on opera performances. The authors analyzed jinghu, erhu, dahu, banhu, and gaohu, as well as outlined the elements that make up the melody for a particular instrument in opera performances. The survey outcomes suggested that improvement of the performance program requires, as part of the staged action: adding a melody that corresponds to the production’s mood (30% of respondents); playing tunes on jinghu more quietly (27% of respondents); removing the tightness when playing banhu (25%); eliminating gaohu (18%). Further survey suggested that melodies were most clearly and correctly played with erhu (27%) and jinghu (23%), with the soft tones and piercing sounds which are typical for these violins. 10% of respondents believed that gaohu was played with many mistakes and was described by a lack of distinctive clear sounds. The respondents’ perceptions of, and playing different violins in, opera suggested that the best quality performance was observed with erhu (0.92), jinghu (0.83), banhu (0.81), and dahu (0.79). The calculation results were compared using the Student’s t-distribution, which suggested the similarity of values for almost all violins, except for gaohu, because playing it in opera performances was not melodious. The research findings are valuable to opera violinists studying the specific features of musical instrument and the harmony of all elements.